Boosting Customer Satisfaction: The Power of Service Quality, Promotion, and Digital Marketing in the Hotel Industry - Aryanti Agustian; M. Yani Syafei; Umi Narimawati (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study investigates the impact of service quality, promotion, and digital marketing on customer satisfaction in the hotel sector in Cikarang. We used a quantitative approach with a survey method, involving 101 hotel customers as respondents. SPSS version 26 software analyzed the data using multiple linear regression. The results show that each independent variable—service quality, promotion, and digital marketing—significantly influences customer satisfaction. Among them, service quality has the strongest impact, followed by promotion and digital marketing. The F test results indicate that these three variables simultaneously affect customer satisfaction, with the calculated F value exceeding the F table and a significance level below 0.05. This suggests that improving service quality, implementing effective promotional strategies, and optimizing digital marketing efforts can significantly enhance customer satisfaction in the hospitality industry in Cikarang. These findings provide valuable insights for hotel managers, highlighting the importance of strengthening these three aspects to increase competitiveness and customer loyalty. By focusing on high-quality service, well-planned promotional activities, and innovative digital marketing, hotels can improve customer experiences, meet their expectations, and build a strong brand reputation. This study underscores the need for continuous improvement in these areas to sustain business growth in an increasingly competitive market.